Electronic government: The level of implementation in the state of Pahang - Othman, Mohd Zainudin; Bidin, Zainol; Othman, Mohd Noor Azman; Abdul Rashid, Mas Anom (2012)
E-government is the use of information communication technology in delivering public service via internet.The Organisation for Economic Cooperation and Development believes that information infrastructures are expected to stimulate economic growth, increase productivity, create jobs and improve the quality of life, and that has been the focus of Malaysian government in upgrading the quality of the citizens’ lives.Sincee government at the state level is equally important to ensure the overall success of Malaysian e-government apart from the federal level, this research has been conducted in Pahang, one of the states in Malaysia, to determine the extent of e-government implemented based on the United Nation E-Government Maturity Stage Model.The study covers the aspects of e-government maturity stage, infrastructure, and website quality.A total of 340 responses were received (77.3% response rate) and the results showed that e-government maturity level in Pahang was at the minimal level of the third stage of the UN-DEPA maturity model, which was the interactive stage.